PEMBINAAN OLIMPIADE SAINS NASIONAL (OSN) BIDANG STUDI MATEMATIKA DI SMP ISLAM TA’ALLUMUL HUDA BUMIAYU - Sudrajat Sudrajat; Fathmi Aqinna Rifqia; Tsalis Rifa Ardiyamti; Intan Sulistyowati (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2025)
Mathematics Olympiad is a competition to measure and improve students' mathematics skills. Therefore, guidance and coaching of mathematics olympiad is needed which aims to prepare superior seeds both in terms of material and mental, especially for students at SMP Islam Ta'allumul Huda Bumiayu in facing mathematics olympiad. The method of implementing this community service uses the method of material consolidation (25%), practice questions (60%), and interviews or moderation (15%). The stages of community service include planning, implementation, evaluation, and reflection. The results achieved in this community service, namely the development of the national science olympiad (OSN) in the field of mathematics study were 100% implemented and students were very enthusiastic in participating in the development of mathematics olympiad. Students' understanding of the olympiad material and various types of mathematics olympiad questions increased significantly, as seen from the results of the pre-test and post-test, namely 80.2 and 90.35 from each sub-chapter of the olympiad material. Students have a competitive spirit and compete intelligently and students have a reference source in the form of drilling mathematics olympiad questions whose credibility has been tested.